Del Escribano Al Secretario Municipal. Antecedentes, Origen y Evolución de Los Cuerpos Nacionales Hasta la Ley de Bases Del Régimen Local - Vera Torrecillas, Rafael Jesús (Dykinson, S.L., 2021)
The book that the reader has in his hands is a study on the process of evolution of the institution of the public scribe of the Council and its transformation into the Town Hall secretary in the 19th century, as well as the evolution of these civil servants until the disappearance of the national public servants of Local Administration and their reconversion into the current civil servants of Local Administration with national qualification. If there is one thing that, over and above the differences between the medieval council clerk and the liberal municipal secretary, both institutions share, it is their central position in the local bureaucracy and the fact that they are depositaries of public faith, which makes them an essential part of the municipal administrative machinery. The author has paid special attention to the main works of historians and jurists who have tackled the study of this institution, attempting to systematise them and identifying future lines of research.